MODEL KONSEPTUAL ADAPTASI RUANG KAMPUNG KOTA SEBAGAI AKIBAT KEBERADAAN SEKTOR PERDAGANGAN FORMAL (KAMPUNG SEKAYU KOTA SEMARANG) - Wulan Dwi Purnamasari (TATALOKA, 2013)
The Growing up of Informal Sector is slowly affected space use and the morphological forms Kampung Sekayu, views of the circulation or movement changes and changes in space for. The model changes of Kampung Sekayu shown in matrix form, diagrams, and mapping by using symbols was adapted from Zahnd theory (2008) which were previously done  uantitative analysis to know the category changes.Based on the theory of Lazarus (1984) about the adjustment, the results of this study shows that the activities of people in Kampung Sekayu is an adaptation because people trying to be part of the formal trade sector that grows rapidly. Each activity requires space as a container. In this case, the changes is happening in Kampung Sekayu is a form of adjustment due to some space available (such as public space) is intended to support the work done by street vendors and parking attendants.